Correlation among some phenological and biochemical traits in date palm (Phoenix dactylifera L.) germplasm - Ahmad, Riaz; Ali, Hayssam M.; Lisek, Anna; Mosa, Walid F. A.; Ercisli, Sezai; Anjum, Muhammad Akbar (Frontiers in Plant Science, 2023)
Date palm is an economically important fruit crop in the arid and semi-arid regions of the world. The knowledge of genetic variation, genotype-by-traits comparison, as well as the relationship among several phenological traits is effective for developing breeding populations by choosing the best allelic combinations and employing selection approaches. Information regarding the genetic variability and inter-relationships among fruit characteristics is facilitating the plant breeders to efficiently exploit the date palm germplasm for the introduction of elite genotypes. The present study was conducted to examine genetic variation among different date palm cultivars -collected from two different research stations in Pakistan as well as the relationship among their phenological and biochemical characteristics. Biplot analysis revealed that the cultivars ‘Dhakki’, ‘Chohara’, and ‘Kupra’ possessed the highest fruit and pulp weights. Moreover, the fruits of the cultivars ‘Champa Kali’ and ‘Shakri’ had the maximum TSS (total soluble solids) and total sugar content. Similar variations were observed in the mean values of the studied phenological and biochemical characteristics as in the biplot analysis. Cluster analysis on the basis of phenological and biochemical characteristics divided 50 cultivars into seven clusters, showing differences in the studied characters. A correlation matrix revealed that pulp weight had a strong relationship with fruit weight, length, and diameter. A strong correlation also existed among antioxidant capacity, antioxidant activity, and total phenolic content. These results demonstrated a huge diversity in phenological and biochemical characteristics of date palm cultivars as well as a correlation among several characteristics of the studied germplasm, which can be exploited in future breeding programs.